PENERAPAN PENDEKATAN DEEP LEARNING PADA MATA PELAJARAN IPAS SISWA KELAS IV MI ISLAM PURWOKERTO SRENGAT BLITAR - Muhammad Tsaba Syafi'uddin; Maftucha (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study is motivated by the implementation of the Merdeka Curriculum, which emphasizes meaningful learning and deep conceptual understanding, while in practice, IPAS learning at the Madrasah Ibtidaiyah level remains teacher-centered and focused on memorization, resulting in low student engagement and conceptual comprehension. This study aims to describe the planning, implementation, and evaluation of the Deep Learning approach in IPAS learning for fourth-grade students at MI Islam Purwokerto Srengat Blitar. This research employs a qualitative approach with a descriptive design. Data collection techniques include observation, interviews, and documentation involving fourth-grade teachers and students. Data were analyzed through data reduction, data display, and conclusion drawing, while validity was ensured through source and technique triangulation. The results indicate that the implementation of the Deep Learning approach is carried out through three stages: planning, implementation, and evaluation. In the planning stage, teachers design lesson plans that encourage active student participation. In the implementation stage, learning activities involve group discussions, observations, questioning, and problem-solving related to real-life contexts. The evaluation stage assesses both the learning process and outcomes reflecting students’ conceptual understanding. The findings show that the Deep Learning approach creates a more active and meaningful learning process, improves critical thinking skills, and strengthens the connection between learning materials and students’ real-life experiences.